1994
DOI: 10.1007/bf02648162
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia in adults: Evidence for deficits in non-word reading and in the phonological representation of lexical items

Abstract: Difficulties in reading and language skills which persist from childhood into adult life are the concerns of this article. The aims were twofold: (1) to find measures of adult reading processes that validate adults' retrospective reports of difficulties in learning to read during the school years, and (2) to search for indications of basic deficits in phonological processing that may point toward underlying causes of reading difficulties. Adults who reported a history of difficulties in learning to read (n=102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
147
1
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 21 publications
17
147
1
6
Order By: Relevance
“…Specific problems in representing phonology have been attributed to dyslexics (Elbro et al, 1994;Elbro & Jensen, 2005;Snowling, et al, 1986). Elbro & Jensen (2005) summarize the argument that dyslexics tend to have underspecified phonological representations, which, for example, leads to the production of non-distinct vowels.…”
Section: Differences Between Print and Speech In Learning New Wordsmentioning
confidence: 99%
“…Specific problems in representing phonology have been attributed to dyslexics (Elbro et al, 1994;Elbro & Jensen, 2005;Snowling, et al, 1986). Elbro & Jensen (2005) summarize the argument that dyslexics tend to have underspecified phonological representations, which, for example, leads to the production of non-distinct vowels.…”
Section: Differences Between Print and Speech In Learning New Wordsmentioning
confidence: 99%
“…Many children with reading problems exhibit deficits in the perception of speech sounds (de Weirdt, 1988;Elliott et al, 1989;Watson and Miller, 1993). This has been attributed to inadequate phonological awareness skills and/or difficulties in perceiving brief sounds (including rapid spectral changes) which occur in speech (Golden and Steiner, 1969;Godfrey et al, 1981;Lieberman et al, 1985;Werker and Tees, 1987;Liberman et al, 1989;Reed, 1989;Elbro et al, 1994;Torgesen and Barker, 1995;Kraus et al, 1996;Merzenich et al, 1996;Stark and Heinz, 1996;Tallal et al, 1996;Mody et al, 1997;Schulte-Koerne et al, 1999). Of particular importance for some learning-impaired children is that these perceptual deficits can be absent in quiet, but manifested in noise typical of everyday listening situations (Elliot et al, 1979;Brady et al, 1983;Chermak et al, 1989;Cunningham et al, 2001;Bradlow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown phonological awareness to be strongly related to early reading skills (Bradley & Bryant, 1983;Høien, Lundberg, Stanovich, & Bjaalid, 1995;Liberman, 1973;Perfetti, Beck, Bell, & Hughes, 1987;Wagner & Torgesen, 1987;Wagner, Torgesen, & Rashotte, 1994). There is also evidence that phonological deficits are the critical factor underlying reading problems (Elbro, Nielsen, & Petersen, 1994;Rack, Snowling, & Olson, 1992;Vellutino, Fletcher, Snowling, & Scanlon, 2004). In addition, interventions aimed at the improvement of phonological awareness have been shown to effectively promote learning to read (Lundberg, Frost, & Petersen, 1988;National Institute of Child Health and Human Development, 2000).…”
mentioning
confidence: 97%